Improvements of mechanical properties and specular gloss of polyurethane by modified nanocrystalline cellulose - Hao Zhang; Ying She; Shuping Song; Heyu Chen; Junwen Pu (BioResources, 2012)
In this study, the optical and mechanical properties of polyurethane were improved by modified nanocrystalline cellulose (NCC). The surface of NCC was modified by 3-glycidoxypropyltrimethoxysilane (GPTMS) and 3-methacryloxy-propyltrimethoxysilane (MPS) to overcome the lack of compatibility with polyurethane. Polyurethane with modified NCC was characterized by wetting property, X-ray powder diffraction, and thermogravimetric analysis. The pencil hardness, specular gloss, and abrasion resistance of modified polyurethane were determined using the methods of Chinese National Standards GB/T 6739-2006, GB/T 9754-2007, and GB/T 1768-2006. The wetting property of NCC modified by GPTMS increased by 25.9%, and modification from MPS resulted in a 22.5% decrease of the contact angle. MPS-modified NCC affected the crystal structure and thermal stability of polyurethane more significantly than NCC modified by GPTMS. The pencil hardness of polyurethane was enhanced with 1.5% modified NCC. The specular gloss and abrasion resistance of modified polyurethane increased by 253.1% (1.0% NCC modified by GPTMS) and 59.4% (1.5% NCC modified by GPTMS), respectively. MPS-modified NCC led to the inconspicuous improvements.